Seismic Vulnerability Assessment of Regular and Vertically Irregular Residential Buildings in Nepal - Satish Paudel; Taufiq Ilham Maulana; Hakas Prayuda (Journal of the Civil Engineering Forum, 2024)
The need to assess the vulnerability of non-engineered residential RCC buildings in Nepal has become urgent, especially considering the ongoing modifications and additions to these structures without understanding their susceptibility to seismic events. Many residential buildings, particularly those up to three stories, did not fully comply to the guidelines outlined in Nepal Building Code NBC 105:2020. Therefore, there is a necessity to assess the seismic performance of these structures. This study aims to quantify the seismic vulnerability of such buildings by focusing on three distinct types: regular two and three-story structures, and irregular three-story structures. Using finite element modeling, the analysis of the buildings’ seismic capacity was performed through pushover analysis. Subsequently, linear time history analysis is conducted to determine the seismic demand. Two software were utilized to conduct the analyses, namely SAP2000 and STERA_3D. The study also includes the matching eleven strong ground motion inputs to Nepal’s site characteristics and response spectrum to ensure the relevance of the local context. Furthermore, fragility curves are constructed to compare the probability of structural failure, by first conducting the nonlinear dynamic analyses on the building specimens. The result showed that the probability of complete failure rises rapidly when an additional story is constructed with vertical irregularity, increasing from 1.8% to 5.7% in a non-engineered two-story building. The study also observes variations in top displacement across all three buildings due to differences in earthquake duration and frequency. From the findings, it is revealed that a significant increase in seismic vulnerability for vertically irregular buildings compared to regular ones